A case of pulmonary tumoral thrombotic microangiopathy supported by VA-ECMO and a review of the literature. Issue 3 (September 2021) - To, Harmony Hau Man; Mak, William Wai Lun; Chan, Tsz Ho; Fong, Man Chi; Mak, Kwok Shing; Yuen, Wing Nam; Mak, Siu Ming; Lam, Cheuk Sum; Chan, Yu Ho
Abstract: We report a case of pulmonary tumoral thrombotic microangiopathy (PTTM) of pancreatobiliary origin who presented with fulminant right heart failure and was revived by extracorporeal membrane oxygenation-cardiopulmonary resuscitation (ECMOCPR). Pathology of PTTM was illustrated. This case highlights the notorious difficulty of antemortem diagnosis of PTTM as well as the role of venoarterial-ECMO as a temporizing measure to diagnosis and treatment. <Learning objective: Pulmonary tumoral thrombotic microangiopathy should be considered in middle-aged patients with pulmonary hypertension with seemingly negative workup results before the diagnosis of idiopathic pulmonary hypertension is accepted. Venoarterial extracorporeal membrane oxygenation is an effective temporizing strategy for this rapidly progressive disease.>